Literasi Digital dan Etika Komunikasi dalam Konteks Media Sosial - M. Alfazri; Jaka Syahputra (JURNAL SYIAR-SYIAR, 2024)
Social media has emerged as a contemporary digital phenomenon that transforms the paradigm of communication and social interaction. This research aims to explore the complexity of social media from technological, social, and ethical perspectives. Utilizing a mixed-methods approach with a descriptive-exploratory design, the study analyzes data from the 2024 APJII survey and various documentary sources. Research findings demonstrate that social media possesses unique characteristics: participatory, open, and interconnected, which facilitate cross-geographical interaction. Key discoveries reveal that 40% of the Indonesian population are active social media users, with platforms such as Facebook and WhatsApp dominating the landscape. The research identifies positive and negative impacts of social media usage, including global connectivity opportunities and digital bullying risks. Approximately 49% of users have experienced cyberbullying, signaling the complexity of digital ethics. The study emphasizes the importance of digital literacy, critical awareness, and collective responsibility in managing cyber spaces. Research implications suggest the necessity of a holistic approach in understanding and regulating digital interactions, considering social, technological, and ethical dimensions.